2003
DOI: 10.1007/s00228-003-0598-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and sedative effects in healthy subjects and subjects with impaired liver function after continuous infusion of clomethiazole

Abstract: The reduced clomethiazole clearance in patients with moderate/severe liver impairment seems to call for a reduction of clomethiazole dosage. However, sedation was not observed in this group at the investigated dose level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Inactivation in HLM by CMZ was relatively efficient as determined by k inact /K I ratio of 8.8 ml min 21 nmol 21 (Table 2), and this was primarily a function of its relatively high k inact value, similar to values reported for tienilic acid/CYP2C9, ticlopidine/ CYP2B6, and ritonavir/CYP3A (Obach et al, 2007). Results using rCYP2E1 gave essentially identical values as those found with HLM (Table 2), demonstrating CYP2E1 inactivation occurs without requirement of metabolism by other cytochromes known to metabolize CMZ (Centerholt et al, 2003). The selectivity of CMZ inhibition of CYP2E1 has been partially investigated in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Inactivation in HLM by CMZ was relatively efficient as determined by k inact /K I ratio of 8.8 ml min 21 nmol 21 (Table 2), and this was primarily a function of its relatively high k inact value, similar to values reported for tienilic acid/CYP2C9, ticlopidine/ CYP2B6, and ritonavir/CYP3A (Obach et al, 2007). Results using rCYP2E1 gave essentially identical values as those found with HLM (Table 2), demonstrating CYP2E1 inactivation occurs without requirement of metabolism by other cytochromes known to metabolize CMZ (Centerholt et al, 2003). The selectivity of CMZ inhibition of CYP2E1 has been partially investigated in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…plasma concentrations occur approximately 1 hour after administration, with an elimination half-life of about 4 hours (Rätz et al, 1999). Clearance is hepatic blood-flow limited and occurs primarily through metabolism by CYP2A6, CYP3A4/5, and CYP2B6 (Centerholt et al, 2003) and CYP2E1 (data not shown). Compared with drugfree volunteers, the AUC of chlorzoxazone, given in a 250-mg dose, increased 3.4-fold in alcoholic patients receiving daily 1.2-2.4 g CMZ at least 1-3 days before chlorzoxazone (Eap et al, 1998).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Patients with moderate/severe liver impairment have reported plasma clearance values approaching 50% of healthy patients (1).…”
Section: Contraindicationsmentioning
confidence: 99%